Preliminary evaluation of plasticizer and BPA in Tunisian cosmetics and investigation of hazards on human skin cells - Beltifa, Asma; Belaid, Afifa; Lo Turco, Vincenzo; Machreki, Monia; Ben Mansour, Hedi; Di Bella, Giuseppa (International journal of environmental health research, 2018)
In this study, 18 plasticizer (phthalates, adipates, sebacates, and others) and BPA residues in some cosmetic samples collected from Tunisian market are evaluated by micro-matrix solid-phase dispersion combined with GC-MS. In parallel, the impact of these molecules and the cosmetics in the human epithelial cell lines is investigated. The cytotoxic activity of cosmetic extracts is evaluated in vitro against B16 and Hep-2 human skin cell lines using the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide assay. This study shows that the tested cosmetic products could constitute a hazard to the consumer health and wellness and that strict safety analysis on cosmetic products needs to be carried out before they are marketed.